(3GdJbQjH hGdEQTGO aj Ydei GdcdGe hGdCUhds - (3eMeO Hf GdXaQ Hf gHI Gddg Hf SQGjG GdebOSjs
(3ChdgG (B:s
(3bGd GdeDda QMeg Gddg JYGdi HGH Gdbhd ai MO GdYde hMbjbJg Ef bGd bGFd eG MO GdYde s
(3BNQgG (B:s
(3jfJgi HBNQ HGH Gdbhd ai GdYGde EPG MUd eYg daX YGe hde jYKQ Ydi eG jhLH hjJdhg ai GdLRA GdKGfi HGH GdcdGe ai CMcGe CaYGd GdQShd UdhGJ Gddg Ydjg s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds